Chromium-nickel modified coating based on laser cladding and preparation method thereof
By adding modified element Pt to the high-temperature coating and preparing the chromium-nickel modified coating by laser cladding, the stability and corrosion resistance of the existing high-temperature coating in high-temperature environments are solved, and the efficient preparation of the coating and excellent corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411889548.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
AI Technical Summary
The existing high-temperature coating has poor stability in steam above 600°C, resulting in loosening and peeling of the oxide film, which in turn causes pipe blockage and pipe burst accidents. The Cr content in the alloy matrix is low, and the corrosion resistance decreases with the increase of service time.
The chromium-nickel modified coating preparation method based on laser cladding is adopted. By adding modified element Pt to the cladding powder, the outer diffusion of alloy base material elements is suppressed, the adhesion of oxide film and base material is enhanced, and the coating is prepared through an integrated laser cladding process production line to ensure efficient preparation and excellent performance of the coating.
It significantly improves the corrosion resistance and peeling resistance of the coating, extends the service life of the coating, and reduces the operating cost and material loss of the boiler unit.
Smart Images

Figure CN119753670A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material surface alloying and coating preparation, and in particular relates to a laser cladding chromium-nickel modified coating. Background Art
[0002] In my country's power industry, pipe blockage and pipe burst accidents caused by corrosion and oxidation of flow-through components account for more than 50% of boiler non-shutdown accidents, resulting in an increase of more than 20% in the operating and material costs of the units; the high-temperature corrosion on the flue gas side of the boiler tubes in coal-fired thermal power plants has become a major hidden danger to the safe operation of the power station, and the corrosion of the metal on the heating surface on the flue gas side is mainly caused by a series of chemical reactions between the material surface and the surrounding corrosive media, such as SO2 in the flue gas formed after the combustion of coal powder, boiler feed water, boiler water, steam, air and fly ash / waste residue, resulting in metal corrosion damage.
[0003] Studies have shown that high-temperature coatings have significant effects in solving the problems of component oxidation corrosion, wear, and high-temperature ablation. At present, the corrosion-resistant coatings for large aspect ratio flow-through components are mainly Cr2O3. However, the stability of Cr2O3 in steam above 600°C is poor, and the loose oxide film caused by volatile products will cause the oxide film to peel off, and further lead to pipe blockage and pipe burst accidents. In addition, the Cr content in the alloy matrix is relatively low. With the increase of service time, when the Cr content required for the growth of the oxide film cannot be supplemented, the corrosion resistance of the alloy will also drop sharply. Therefore, it is of great practical significance to study and develop corrosion-resistant and oxidation-resistant coatings suitable for the inner and outer wall surfaces of pipelines for boiler units. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a chromium-nickel modified coating based on laser cladding.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0008] The solid phase cladding powder and the liquid phase binder are mixed, stirred and ball-milled to obtain the cladding slurry;
[0009] The cladding slurry is evenly sprayed onto the preheated workpiece surface to form a prefabricated slurry layer. The dried and solidified workpiece is placed in an inert atmosphere for laser cladding treatment. After treatment, it is cooled and the residue is treated to form a chromium-nickel modified coating on the workpiece surface.
[0010] Wherein, in terms of mass percentage, the solid phase cladding powder includes 40 to 70 parts of Cr, 20 to 50 parts of Ni, 3 to 6 parts of Pt, 3 to 6 parts of Hf and 1 to 5 parts of NH4Cl.
[0011] As a preferred solution of the method for preparing the chromium-nickel modified coating based on laser cladding described in the present invention, wherein: the liquid phase binder is ethyl acetate.
[0012] As a preferred solution of the method for preparing the chromium-nickel modified coating based on laser cladding of the present invention, the amount of the liquid phase binder is 10-30% of the mass of the solid phase cladding powder.
[0013] As a preferred solution of the method for preparing the chromium-nickel modified coating based on laser cladding of the present invention, the mixing time of the solid-phase cladding powder and the liquid-phase binder is 2 to 4 hours.
[0014] As a preferred embodiment of the method for preparing the chromium-nickel modified coating based on laser cladding of the present invention, the ball milling speed of the solid-phase cladding powder and the liquid-phase binder is 350-400 rpm and the time is 8-12 hours.
[0015] As a preferred solution of the method for preparing the chromium-nickel modified coating based on laser cladding described in the present invention, the preheating treatment is medium frequency preheating at 200-250° C. for 30-60 minutes.
[0016] As a preferred solution of the method for preparing the chromium-nickel modified coating based on laser cladding of the present invention, the thickness of the prefabricated slurry layer is 1 to 5 mm, and the coating coverage is not less than 98%.
[0017] As a preferred embodiment of the method for preparing the chromium-nickel modified coating based on laser cladding of the present invention, the drying is natural drying for 24 to 48 hours, and the curing is curing at 300 to 450° C. for 24 to 48 hours.
[0018] As a preferred scheme of the preparation method of the chromium-nickel modified coating based on laser cladding described in the present invention, wherein: the laser cladding treatment, wherein the laser power is 2-2.8KW, the scanning rate is 20-40mm / s, the spot diameter is 3-5mm, the workpiece rotation speed is 3-6r / min, and the Ar gas flow rate is 15-20L / min.
[0019] Another object of the present invention is to provide a chromium-nickel modified coating prepared by a preparation method of a chromium-nickel modified coating based on laser cladding.
[0020] Beneficial effects of the present invention:
[0021] (1) The chromium-nickel modified coating based on laser cladding provided by the present invention can inhibit the outward diffusion of alloy base material elements by adding the modifying element Pt to the cladding powder component, improve the adhesion between the oxide film and the base material, enhance the anti-stripping performance of the coating, and thus improve the corrosion resistance.
[0022] (2) The present invention prepares the coating through an integrated laser cladding process production line. The process has concentrated heat, short action time, small thermal impact in the cladding zone, high coating production efficiency, controllable thickness, high process repeatability, and is extremely practical and universal.
[0023] (3) The present invention adopts a segmented slurry curing process that combines natural air drying with medium and low temperature curing, which effectively avoids the problem of microcracks and tiny holes in the slurry layer caused by thermal stress during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0025] Figure 1 This is the cross-sectional morphology of the chromium-nickel modified coating prepared in Example 1 of the present invention.
[0026] Figure 2 This is a line scan diagram of the Cr content in the infiltration layer of the sample prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0030] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.
[0031] The method for measuring the thickness of the permeable layer in the present invention refers to:
[0032] The thickness of the infiltration layer was measured by scanning electron microscope (SEM) and backscattering HDBSD (Zeiss-Sigma HD).
[0033] Corrosion resistance test reference:
[0034] Place the sample in a flue gas environment at 650°C for 200 hours and measure the weight loss / mg / cm 3 .
[0035] Example 1
[0036] This embodiment provides a method for preparing a chromium-nickel modified coating based on laser cladding, specifically:
[0037] 1) 40 parts of Cr, 50 parts of Ni, 3 parts of Pt, 6 parts of Hf and 1 part of NH4Cl were placed in a planetary ball mill and milled at a speed of 400 rpm for 12 hours to obtain a solid phase cladding powder, which was sieved through a 1000 mesh screen;
[0038] Add 10% ethyl acetate compared to the solid phase cladding powder, stir thoroughly for 4 hours, and then place in a planetary ball mill at a speed of 400 rpm for 12 hours to obtain a cladding slurry;
[0039] 2) The surface of the workpiece to be processed is cleaned with a high-pressure water gun for 5 minutes, and then rinsed with alcohol or acetone, and preheated at 250°C for 45 minutes by medium frequency to obtain a preheated workpiece;
[0040] The cladding slurry is evenly sprayed onto the surface of the preheated workpiece to form a prefabricated slurry layer with a thickness of 3 mm and a slurry coverage rate of not less than 98%;
[0041] 3) The workpiece was naturally air-dried for 48 hours and cured at 450°C for 48 hours. After curing, the workpiece was placed under Ar for laser cladding. The laser power was 2.6KW, the scanning rate was 25mm / s, the spot diameter was 3mm, the workpiece rotation speed was 5r / min, and the Ar gas flow rate was 15L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was washed with high-pressure air flow, that is, a chromium-nickel modified coating was formed on the surface of the workpiece. Its morphology is as follows Figure 1 shown.
[0042] Example 2
[0043] The difference between this embodiment and embodiment 1 is that the parameters of laser cladding are adjusted, and the remaining steps and processes are referred to embodiment 1, and the chromium-nickel modified coatings prepared with different laser cladding parameters are obtained, and the thickness of the diffusion layer is measured. The laser cladding parameters and the corresponding coating thickness are shown in Table 1.
[0044] Table 1 Coating thickness of chromium-nickel modified coating under different laser cladding parameters
[0045]
[0046]
[0047] It can be seen from Table 1 that the thickness of the infiltrated layer under different laser cladding conditions is 0.17-0.81 mm. The cross-sectional morphology of the laser cladding chromium-nickel modified coating prepared in Example 1 is as follows: Figure 1 As shown, the thickness of the diffusion layer of the sample prepared in Example 1 is specifically 171.6 μm. Figure 2 The figure shows the line scan of the Cr content in the infiltration layer of the sample prepared in Example 1. It can be seen that the Cr content increases uniformly from the infiltration layer to the matrix. Figure 1 , 2 It can be seen that the infiltration layer has a uniform structure and moderate thickness, and the infiltration layer has a good metallurgical bond with the matrix and is not easy to fall off.
[0048] Corrosion resistance tests show that different laser cladding conditions have a certain influence on coating performance. In order to obtain a coating with optimal corrosion resistance, appropriate laser cladding conditions need to be selected.
[0049] Example 3
[0050] 1) 70 parts of Cr, 20 parts of Ni, 6 parts of Pt, 3 parts of Hf and 1 part of NH4Cl were placed in a planetary ball mill and milled at a speed of 400 rpm for 12 hours to obtain a solid phase cladding powder;
[0051] Add 30% ethyl acetate compared to the solid phase cladding powder, stir thoroughly for 2 hours, and then place in a planetary ball mill at a speed of 400 rpm for 12 hours to obtain a cladding slurry;
[0052] 2) The surface of the workpiece to be processed is cleaned with a high-pressure water gun for 5 minutes, and then rinsed with alcohol or acetone, and preheated at 200°C for 60 minutes by medium frequency to obtain a preheated workpiece;
[0053] The cladding slurry is evenly sprayed onto the surface of the preheated workpiece to form a prefabricated slurry layer with a thickness of 5 mm and a slurry coverage rate of not less than 98%;
[0054] 3) The workpiece was naturally air-dried for 24 hours and cured at 300°C for 48 hours. After curing, the workpiece was placed under Ar for laser cladding. The laser power was 2.5KW, the scanning rate was 20mm / s, the spot diameter was 2mm, the workpiece rotation speed was 5r / min, and the Ar gas flow rate was 15L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow to form a chromium-nickel modified coating on the surface of the workpiece.
[0055] Example 4
[0056] 1) 50 parts of Cr, 35 parts of Ni, 5 parts of Pt, 5 parts of Hf and 5 parts of NH4Cl were ball milled at 400 rpm in a planetary ball mill for 24 hours to obtain a solid phase cladding powder;
[0057] Add 20% ethyl acetate compared to the solid phase cladding powder, stir thoroughly for 2 hours, and then place in a planetary ball mill at a speed of 350 rpm for 8 hours to obtain a cladding slurry;
[0058] 2) The surface of the workpiece to be processed is cleaned with a high-pressure water gun for 5 minutes, and then rinsed with alcohol or acetone, and preheated at 250°C for 30 minutes by medium frequency to obtain a preheated workpiece;
[0059] The cladding slurry is evenly sprayed onto the surface of the preheated workpiece to form a prefabricated slurry layer with a thickness of 5 mm and a slurry coverage rate of not less than 98 parts;
[0060] 3) The workpiece was naturally air-dried for 24 hours and cured at 450°C for 48 hours. After curing, the workpiece was placed under Ar for laser cladding. The laser power was 2.8KW, the scanning rate was 40mm / s, the spot diameter was 3mm, the workpiece rotation speed was 2r / min, and the Ar gas flow rate was 15L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow to form a chromium-nickel modified coating on the surface of the workpiece.
[0061] Example 5
[0062] 1) 55 parts of Cr, 35 parts of Ni, 3 parts of Pt, 5 parts of Hf and 2 parts of NH4Cl were ball milled at 400 rpm for 12 hours in a planetary ball mill to obtain a solid phase cladding powder;
[0063] Add 20% ethyl acetate compared to the solid phase cladding powder, stir thoroughly for 2 hours, and then place in a planetary ball mill at a speed of 350 rpm for 12 hours to obtain a cladding slurry;
[0064] 2) The surface of the workpiece to be processed is cleaned with a high-pressure water gun for 5 minutes, and then rinsed with alcohol or acetone, and preheated at 200°C for 60 minutes by medium frequency to obtain a preheated workpiece;
[0065] The cladding slurry is evenly sprayed onto the preheated workpiece surface to form a prefabricated slurry layer with a thickness of 5 mm and a slurry coverage rate of not less than 98%;
[0066] 3) The workpiece was naturally air-dried for 24 hours and cured at 400°C for 48 hours. After curing, the workpiece was placed under Ar for laser cladding. The laser power was 2.8KW, the scanning rate was 20mm / s, the spot diameter was 3mm, the workpiece rotation speed was 5r / min, and the Ar gas flow rate was 15L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow to form a chromium-nickel modified coating on the surface of the workpiece.
[0067] Example 6
[0068] 1) 55 parts of Cr, 34 parts of Ni, 4 parts of Pt, 4 parts of Hf and 3 parts of NH4Cl were ball milled at 400 rpm in a planetary ball mill for 24 hours to obtain a solid phase cladding powder;
[0069] Add 30% ethyl acetate compared to the solid phase cladding powder, stir thoroughly for 2 hours, and then place in a planetary ball mill at a speed of 400 rpm for 12 hours to obtain a cladding slurry;
[0070] 2) The surface of the workpiece to be processed is cleaned with a high-pressure water gun for 5 minutes, and then rinsed with alcohol or acetone, and preheated at 250°C for 45 minutes by medium frequency to obtain a preheated workpiece;
[0071] The cladding slurry is evenly sprayed onto the surface of the preheated workpiece to form a prefabricated slurry layer with a thickness of 5 mm and a slurry coverage rate of not less than 98%;
[0072] 3) The workpiece was naturally air-dried for 24 hours and cured at 4050°C for 48 hours. After curing, the workpiece was placed under Ar for laser cladding. The laser power was 2KW, the scanning rate was 30mm / s, the spot diameter was 5mm, the workpiece rotation speed was 5r / min, and the Ar gas flow rate was 18L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow to form a chromium-nickel modified coating on the surface of the workpiece.
[0073] Example 7
[0074] 1) 45 parts of Cr, 45 parts of Ni, 4 parts of Pt, 4 parts of Hf and 2 parts of NH4Cl were ball milled at 350 rpm for 12 h in a planetary ball mill to obtain a solid phase cladding powder;
[0075] Add 30% ethyl acetate compared to the solid phase cladding powder, stir thoroughly for 2 hours, and then place in a planetary ball mill at a speed of 400 rpm for 8 hours to obtain a cladding slurry;
[0076] 2) The surface of the workpiece to be processed is cleaned with a high-pressure water gun for 5 minutes, and then rinsed with alcohol or acetone, and preheated at 250°C for 60 minutes by medium frequency to obtain a preheated workpiece;
[0077] The cladding slurry is evenly sprayed onto the surface of the preheated workpiece to form a prefabricated slurry layer with a thickness of 4 mm and a slurry coverage rate of not less than 98%;
[0078] 3) The workpiece was naturally air-dried for 36 hours and cured at 450°C for 48 hours. After curing, the workpiece was placed under Ar for laser cladding. The laser power was 2.8KW, the scanning rate was 40mm / s, the spot diameter was 5mm, the workpiece rotation speed was 4r / min, and the Ar gas flow rate was 20L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was washed with high-pressure airflow to form a chromium-nickel modified coating on the surface of the workpiece.
[0079] Example 8
[0080] 1) 58 parts of Cr, 32 parts of Ni, 2 parts of Pt, 4 parts of Hf and 4 parts of NH4Cl were ball milled at 350 rpm for 24 hours in a planetary ball mill to obtain a solid phase cladding powder;
[0081] Add 20% ethyl acetate compared to the solid phase cladding powder, stir thoroughly for 4 hours, and then place in a planetary ball mill at a speed of 400 rpm for 8 hours to obtain a cladding slurry;
[0082] 2) The surface of the workpiece to be processed is cleaned with a high-pressure water gun for 5 minutes, and then rinsed with alcohol or acetone, and preheated at 250°C for 60 minutes by medium frequency to obtain a preheated workpiece;
[0083] The cladding slurry is evenly sprayed onto the surface of the preheated workpiece to form a prefabricated slurry layer with a thickness of 5 mm and a slurry coverage rate of not less than 98%;
[0084] 3) The workpiece was naturally air-dried for 48 hours and cured at 450°C for 48 hours. After curing, the workpiece was placed under Ar for laser cladding. The laser power was 2.8KW, the scanning rate was 40mm / s, the spot diameter was 4mm, the workpiece rotation speed was 4r / min, and the Ar gas flow rate was 15L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was washed with high-pressure airflow to form a chromium-nickel modified coating on the surface of the workpiece.
[0085] Example 9
[0086] 1) 55 parts of Cr, 35 parts of Ni, 4 parts of Pt, 2 parts of Hf and 4 parts of NH4Cl were ball milled at 400 rpm for 24 hours in a planetary ball mill to obtain a solid phase cladding powder;
[0087] Add 30% ethyl acetate compared to the solid phase cladding powder, stir thoroughly for 4 hours, and then place in a planetary ball mill at a speed of 400 rpm for 8 hours to obtain a cladding slurry;
[0088] 2) The surface of the workpiece to be processed is cleaned with a high-pressure water gun for 5 minutes, and then rinsed with alcohol or acetone, and preheated at 250°C for 60 minutes by medium frequency to obtain a preheated workpiece;
[0089] The cladding slurry is evenly sprayed onto the surface of the preheated workpiece to form a prefabricated slurry layer with a thickness of 5 mm and a slurry coverage rate of not less than 98%;
[0090] 3) The workpiece was naturally air-dried for 24 hours and cured at 450°C for 48 hours. After curing, the workpiece was placed under Ar for laser cladding. The laser power was 2.8KW, the scanning rate was 35mm / s, the spot diameter was 4mm, the workpiece rotation speed was 2r / min, and the Ar gas flow rate was 18L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow to form a chromium-nickel modified coating on the surface of the workpiece.
[0091] The thickness of the coatings prepared in Examples 3 to 9 and the corrosion resistance of the coatings (weight loss after 650° C. flue gas corrosion for 500 h) were measured and compared with Example 1. The results are shown in Table 2.
[0092] Table 2
[0093]
[0094] It can be seen from Table 2 that a cladding layer with excellent effect can be prepared by changing the Cr, Ni content and the thickness of the slurry layer within a certain range. Therefore, the chromium-nickel modified coating by laser cladding in the present invention is suitable for austenitic steel and high-temperature alloy parts used in large boilers, oil and gas field transportation pipelines and various complex-shaped workpieces. It has strong practicality, high permeation rate, excellent membrane-base bonding, and excellent industrial mass production benefits.
[0095] Comparative Example 1
[0096] The difference between this comparative example and Example 1 is that Pt in the solid phase cladding powder is omitted, and the remaining steps are the same as those in Example 1 to obtain the chromium-nickel modified coating of this comparative example.
[0097] Comparative Example 2
[0098] The difference between this comparative example and Example 1 is that NH4Cl in the solid phase cladding powder is omitted, and the remaining steps are the same as those in Example 1 to obtain the chromium-nickel modified coating of this comparative example.
[0099] Comparative Example 3
[0100] The difference between this comparative example and Example 1 is that Hf in the solid phase cladding powder is omitted, and the remaining steps are the same as those in Example 1 to obtain the chromium-nickel modified coating of this comparative example.
[0101] The coating thickness and corrosion resistance of Comparative Examples 1 to 3 were tested and compared with Example 1. The results are shown in Table 3.
[0102] Table 3
[0103] Test Project Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Weight loss in mg / cm after 500 h of flue gas corrosion at 650 °C 2 > 0.11 3.6 0.893 0.945 Cladding layer thickness / mm 0.81 0.03 0.12 0.11
[0104] It can be seen from Table 3 that NH4Cl, Pt and Hf all play a positive role in the formation of the cladding layer during the preparation process of the cladding layer, thereby improving the smoke corrosion resistance of the cladding layer.
[0105] In summary, the chromium-nickel modified coating based on laser cladding provided by the present invention can inhibit the outward diffusion of alloy base material elements by adding the modifying element Pt to the cladding powder component, improve the adhesion between the oxide film and the base material, enhance the anti-stripping performance of the coating, and thus improve the corrosion resistance.
[0106] The present invention prepares the coating through an integrated laser cladding process production line. The process has concentrated heat, short action time, small thermal impact in the cladding zone, high coating production efficiency, controllable thickness, high process repeatability, and extremely strong practicality and universality.
[0107] The present invention adopts a segmented slurry curing process combining natural air drying with medium and low temperature curing, which effectively avoids the problem of micro cracks and tiny holes in the slurry layer caused by thermal stress during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface.
[0108] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a chromium-nickel modified coating based on laser cladding, characterized in that: include, The solid phase cladding powder and the liquid phase binder are mixed, stirred and ball-milled to obtain the cladding slurry; The cladding slurry is evenly sprayed onto the preheated workpiece surface to form a prefabricated slurry layer. The dried and solidified workpiece is placed in an inert atmosphere for laser cladding treatment. After treatment, it is cooled and the residue is treated to form a chromium-nickel modified coating on the workpiece surface. Among them, by mass, it includes 40-70 parts of Cr, 20-50 parts of Ni, 3-6 parts of Pt, 3-6 parts of Hf and 1-5 parts of NH4Cl.
2. The method for preparing a chromium-nickel modified coating based on laser cladding according to claim 1, characterized in that: The liquid phase binder is ethyl acetate.
3. The method for preparing a chromium-nickel modified coating based on laser cladding according to claim 2, characterized in that: The amount of the liquid phase binder used is 10-30% of the mass of the solid phase cladding powder.
4. The method for preparing a chromium-nickel modified coating based on laser cladding according to claim 1, characterized in that: The solid-phase cladding powder and the liquid-phase binder are mixed and stirred for 2 to 4 hours.
5. The method for preparing a chromium-nickel modified coating based on laser cladding according to claim 1, characterized in that: The solid phase cladding powder and the liquid phase binder are ball milled at a speed of 350-400 rpm for 8-12 hours.
6. The method for preparing a chromium-nickel modified coating based on laser cladding according to claim 1, characterized in that: The preheating treatment is medium frequency preheating at 200-250° C. for 30-60 minutes.
7. The method for preparing a chromium-nickel modified coating based on laser cladding according to claim 1, characterized in that: The thickness of the prefabricated slurry layer is 1-5 mm, and the coating coverage is not less than 98%.
8. The method for preparing a chromium-nickel modified coating based on laser cladding according to claim 1, characterized in that: The drying is natural drying, the drying time is 24 to 48 hours, and the curing is curing at 300 to 450° C. for 24 to 48 hours.
9. The method for preparing a chromium-nickel modified coating based on laser cladding according to claim 1, characterized in that: The laser cladding process comprises the following steps: the laser power is 2-2.8 kW, the scanning rate is 20-40 mm / s, the spot diameter is 3-5 mm, the workpiece rotation speed is 3-6 r / min, and the Ar gas flow rate is 15-20 L / min.
10. The chromium-nickel modified coating prepared by the preparation method according to any one of claims 1 to 9.